Effect of the Rectify on the Energy Separation Performance of the Vortex Tube - 何曙; 郭建; 吴玉庭; 丁雨; 马重芳; 葛满初 (Zhileng xuebao)
Rectifies of various guide vane angles which is used in vortex tube had been designed and fabricated.A reliable test rig had been designed and constructed to investigate the effect of rectify and its vane angle on the energy separation performance,rectify on the length/diameter ratio of a vortex tube system.The comparison experiments have been carried out using the aforesaid vortex tube and the tube of the same type made in ARTX Company.The results show that the unit refrigeration of the vortex tube with the rectify is increased by 12%~44% than that without rectify when the cold mass flow ratio is 50%~80%,the bigger angle of the rectify the better refrigeration effect is got with the cold mass flow ratio less than 70%,the length/diameter ratio of the vortex tube with rectify is decreased 6.4 times without impairing the refrigeration,and the aforesaid vortex tube gets better refrigeration effect than that made in ARTX company when the cold mass flow ratio is bigger than 60%..